The role and importance of the agrarian sector in the development of the national economy - Bodaukhan, K.; Kunurkulzhaeva, G.T.; Taskarina, B.M.; Bolatova, B.Zh. (BUKETOV BUSINESS REVIEW, 2019)
The purpose of the research is to substantiate the macroeconomic importance of the agricultural sector of Kazakhstan in the development of the national economy, both from a theoretical and from a practical point of view. In the article current issues and problems of development of the agrarian sector of Kazakhstan in the modern conditions of the functioning of the national economy as a whole are considered. The macroeconomic role and importance of the agrarian sector and the agro-industrial complex of the Republic of Kazakhstan are substantiated; the features of agrarian production are studied. The measures and methods of state support of the agrarian sector in the framework of government programs implemented in the country are considered. Priority areas of state regulation of this sphere in the implementation of agricultural policy are identified. Also, the article touched upon the issues of crediting and subsidizing of business entities. As we know, the agrarian sector occupies a special place in the economy of any country. In the future, in many positions of the agro-industrial complex of Kazakhstan can become one of the world's largest producers of agrarian export products. New global economic challenges and the instability of the conjuncture in the commodity markets dictate the need to address the primary task - the diversification of the economy. In achieving this objective, the key role is played by the agrarian sector, which is considered as one of the drivers of structural reforms of the economy and its growth.